Counseling and Guided Self‐Help Outcomes for Clients With Bulimia Nervosa: A Meta‐Analysis of Clinical Trials From 1980 to 2010. (5th March 2013) - Erford, Bradley T.; Richards, Taryn; Peacock, Elizabeth; Voith, Karen; McGair, Heather; Muller, Brooke; Duncan, Kelly; Chang, Catherine Y.
<x xml:space="preserve">Abstract</x> This meta‐analysis included 111 clinical trials exploring the effectiveness of counseling/psychotherapy and guided self‐help approaches in the treatment of bulimia nervosa. In general, single‐group studies supported higher efficacy of counseling/psychotherapy, whereas wait‐list, treatment‐as‐usual, and placebo studies indicated both approaches were equally effective at termination (posttest) and follow‐up in altering binging, purging, laxative use, and self‐reported bulimia or body dissatisfaction perceptions in nearly all comparisons.